PERLINDUNGAN HUKUM DAN PEMBERDAYAAN BURUH DALAM MEMPEROLEH HAK KEHIDUPAN YANG LAYAK - Lamijan Undaris (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
This research aims to answer the question: How is legal protection for workers to obtain the rights to a decent life, and how are the efforts to empower workers so that they can obtain decent life rights?This research is juridical-normative or doctrinal, in the study of socio-legal data explanation. This research data is obtained through document or literature study, in the form of legal materials, namely primary legal materials and secondary legal materials. Data analysis was carried out by descriptive-qualitative.The results of this study indicate that legal protection for workers is carried out through various reconstructions, namely the regulation of independent and neutral labor unions, regulation of industrial relations based on partnership patterns, regulation of labor wages that meet the needs of a decent life, eliminating regulations on the contract work system (outsourcing), and setting up a social security system for workers and their families. On the other hand, efforts to empower workers are carried out in various ways to obtain their rights, namely the right to get education and skills, the right to get a job according to their expertise, the right to work safety and health, the right to practice worship according to their religion, the right to earn decent income for their lives, the right to associate and the right to convey aspirations.Keywords: labor, protection, empowerment, decent life